Application of Luminescent Microscopy in Analysis of Anatomic-diagnostic Signs of Fruits of Sea Buckthorn - O. V. Trineeva; A. A. Gudkova; M. A. Rudaya (Разработка и регистрация лекарственных средств)
Introduction. Sea buckthorn (Hippophae rhamnoides), the family Eleagnaceae – a promising source of biologically active substances, the traditional raw materials of which are fruits. The existing regulatory documentation (ND) lacks such an indicator of the authenticity and good quality of the fruit as «microscopy». Despite the available data on the anatomy and histology of the fruits of this type of medicinal plant material (MPM), the scientific literature does not describe the luminescence features of the tissues of sea buckthorn fruit. It is known that the luminescent features of tissues make it possible to identify the localization of biologically active structures, and also, in some cases, to conduct selective diagnosis of MPM.Aim. The aim of this work was to study the characteristics of the luminescence of the tissues of dried crushed fruits of sea buckthorn, and also to optimize the conditions for analysis.Materials and methods. The object of the study was the dried, crushed fruits of sea buckthorn of various species. The study of microdiagnostic signs was carried out according to the State Pharmacopoeia of the XIV RF GPA.1.5.3.0003.15 «Technique of microscopic and microchemical studies of medicinal plant materials and herbal medicines». A stereomicroscopic study was carried out on a Biomed-6 microscope. The luminescence of sea buckthorn fruit tissues was examined using a luminescent microscope of the Micromed-3 Lum brand.Results and discussion. The most pronounced yellow glow is observed for the tissue of the pulp and epidermis of the fetus, which is associated with the highest content of fatty oil in these structures. Groups of phenolic compounds contained along with oil give a greenish tint to objects, while condensed tannins give a brownish tint. The plates that make up the corymbose hairs do not exhibit bright luminescence; a weak glow is characteristic of the joints of the hair platelets. The walls of stellate hairs have a faint greenish glow. Fragments of the actual fruit («sac») are brownish in color, without their own luminescence, as well as the seed peel. The embryo has its own greenish luminescence due to the presence of both a fatty oil and a complex of storage substances.Conclusion. The luminescent analysis of sea buckthorn fruits was carried out for the first time. The choice of a method for preparing the studied MPM for microscopic examination is experimentally substantiated. The luminescent analysis revealed the peculiarities of the glow of the tissues of the fruits of sea buckthorn. The main microdiagnostic signs of crushed dried sea buckthorn fruits and their biometric characteristics are specified. The analysis of the obtained data will allow us to further develop the section «Microscopic signs» for inclusion in the PA project on MPM, widely cultivated and used by the domestic pharmaceutical industry for the production of herbal medicines.